"Automatic" Output Stability and the Exchange Arrangement: A Multi-Country Analysis - Jones, Michael (Review of Economic Studies, 1982)
The dependence of national output variances on the structural and stochastic features of world markets and on the global exchange arrangement is depicted in a multi-country model of income and exchange rate determination. The set of Pareto optimal exchange arrangements is displayed. Examples are presented to illustrate the empirical determinants of an optimal arrangement, the situations under which currency blocs are Pareto optimal, and the distributional conflicts which often arise in an asymmetric world.